Devices and Designs
XIV, 284 p. 5 illus.
Keywords: In this volume, leading scholars in the history and sociology of medicine focus their attention on the material cultures of health care. They analyze how technology has become so central to medicine over the last two centuries and how we are coping with the consequences.